The Algorithmic Gaze: AI and the Synthetic A Priori of Beauty - AMITABH VIKRAM DWIVEDI (Journal of Dharma, 2025)
This article examines the Kantian account of aesthetic judgment amid the generation and circulation of images through computational systems. Building on Immanuel Kant’s view that judgments of beauty depend on an a priori structure of reflective judgment, the paper advances two related theses. First, contemporary generative models can produce outputs that reliably elicit human experiences of beauty; yet they do so without the subjective purposiveness and intentional directedness that Kant associates with artistic genius. Their operations follow statistical inference and pattern optimization rather than reflective intention. Second, a more consequential transformation occurs at the level of reception: recommendation systems and platform feeds reorganize which forms become visible, repeatable and culturally normative, thereby shaping the dispositions through which aesthetic judgments arise. What appears beautiful is increasingly conditioned by infrastructures that predict, rank, and circulate images at scale. By placing Kant in dialogue with debates on intentionality, media theory and neuroaesthetics, and by drawing on empirical research on algorithmic curation in music streaming and social platforms, the article proposes understanding the aesthetic a priori as technogenetic—historically plastic and increasingly externalized into systems of prediction, optimization and digital mediation. Beauty, therefore, does not disappear but is judged and shared under reconfigured conditions.